B‐type natriuretic peptide trends after pediatric heart transplantation. (12th June 2014) - Sparks, Joshua D.; Boston, Umar; Eghtesady, Pirooz; Canter, Charles E.
Abstract BNP is increasingly utilized in the management of pediatric HT recipients. Performing a retrospective single‐center chart review, we sought to describe BNP changes during the first year after HT and identify factors that affect its trend. After exclusion for rejection, 316 BNP levels from 50 patients were evaluated. BNP underwent an exponential decline 120 days after HT followed by a plateau. Log10BNP decline strongly correlated with time (r = −0.70, p < 0.0001). Initial BNP was less in pretransplant VAD (p = 0.0016) and lower post‐HT inotrope use (p = 0.0043). Infant recipients, IT >4 h, and those bridged medically were associated with higher plateau BNP. Multivariable logistic regression demonstrated IT >4 h independently predicted plateau BNP in the upper quartile (OR 7.1, p = 0.02). No significant change in BNP coincided with rejection (N = 6 patients) without severe hemodynamic compromise. BNP correlated modestly with right atrial pressure (r = 0.4652, p < 0.0001) and pulmonary capillary wedge pressure (r = 0.2660, p < 0.001), but poorly with echocardiogram (r = −0.18, p = 0.003). Trending BNP could help provide insight into how the graft recovers after HT and IT >4 h independently predicted higher plateau BNP and may reflect subtle changes in graft performance.